The Sao Stone Cosmology within the Aman Seri Community in Urimessing - Matakena, Fransina; Watloly, Aholiab (Baileo: Jurnal Sosial Humaniora, 2024)
This study explores the cosmological significance of the Sao Stone within the indigenous Aman Seri community in Urimessing, aiming to reveal the philosophical dimensions of their worldview and its role in sustaining cultural identity and cosmic continuity. Employing a qualitative approach, the research was conducted through fieldwork, including in-depth interviews, guided discussions, and participant observations. The study examines how the cosmological process surrounding the Sao Stone intertwines the development of human beings, the indigenous Aman Seri community, and other cosmic substances in a continuous, layered flow. The findings demonstrate that the Sao Stone is not merely a physical object but a symbol of existential cohesion that shapes and reflects the evolving identity of the Aman Seri cosmos. Its cosmology is marked by two core characteristics: first, the unceasing, accumulative nature of growth across human, communal, and cosmic levels, where each new incident contributes to an ever-renewing heritage; and second, the sequential realization of cosmic elements, indicating a process without abrupt leaps, grounded in the maturity and density of preceding developments. Each stage in the cosmological process holds autonomous significance, while simultaneously depending on the pressure and specificity of the moment it emerges from. The novelty of this research lies in articulating the dynamic and recursive nature of Aman Seri’s cosmology as a framework of cultural resilience and adaptive identity. It contributes to broader discourses in social sciences and the humanities by emphasizing the relevance of indigenous cosmological systems in understanding community-based environmental philosophies, historical endurance, and cultural regeneration. Further studies are encouraged to investigate other cosmological symbols across Maluku that may offer parallel insights into local knowledge systems and their ongoing transformation.